Active Structural Acoustic Control of a Softcore Sandwich Panel Using Multiple Piezoelectric Actuators and Reddy's Higher Order Theory. Issue 4 (December 2015) - Sahu, Kiran Chandra; Tuhkuri, Jukka; Reddy, J. N.
The purpose of the present work is to theoretically investigate the active control of radiated sound power from a simply supported soft-core sandwich panel with a line moment excitation. Since noise transmission in the low frequency region through a soft-core sandwich panel mainly occurs due to flexural and dilatational modes, therefore, the focus of this study is to control these modes and achieve sound attenuation in a large frequency band. Two control methods, volume velocity and weighted sum of spatial gradients (WSSG) are used to drive three piezoelectric actuators (PZTs) attached on the exterior side of the bottom face plate. The governing equation of the sandwich panel with the PZTs is derived using the Hamilton's principle considering Reddy's third order shear deformation theory. Numerical studies indicate that while the line moment is at the mid vertical line, WSSG is able to attenuate the radiated sound power irrespective of core loss factor whereas volume velocity could not. However, both the control metrics are able to attenuate most of the structural modes, when the line moment is off the midline, and therefore, attenuate significant amount of radiated sound power in a broad frequency range. And the maximum increase in sound power is small in WSSG as compared to volume velocity. These results show that WSSG can be used as an effective control metric to mitigate low frequency sound.